2022
DOI: 10.1111/odi.14226
|View full text |Cite
|
Sign up to set email alerts
|

Dental anomalies in non‐syndromic orofacial clefts: A clinical approach

Abstract: Orofacial clefts (OC) represent some of the most common congenital malformations and affect multiple structures in the craniofacial region. There are a wide range of morphological OC types within the spectrum of both non‐syndromic OC (NSOC) and syndromic OC, including cleft lip (CL), cleft lip and palate, (CLP), and cleft palate (CP). Here, we describe the most frequent dental anomalies seen in the permanent dentition of individuals with NSOC, comparing them between the three main cleft types (CL, CLP, and CP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 160 publications
0
4
0
Order By: Relevance
“…Thus, it is possible that disorders in these events may predispose to dental anomalies in individuals with cleft . 29,30 Studies with two and three-dimensional images have identified mandibular asymmetry in patients with unilateral cleft lip and palate 31,32 Changes in mandibular volume were also observed in this type of cleft. 33 Further studies are necessary to relate mandibular changes and dental anomalies, especially root dilaceration in individuals with cleft.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that disorders in these events may predispose to dental anomalies in individuals with cleft . 29,30 Studies with two and three-dimensional images have identified mandibular asymmetry in patients with unilateral cleft lip and palate 31,32 Changes in mandibular volume were also observed in this type of cleft. 33 Further studies are necessary to relate mandibular changes and dental anomalies, especially root dilaceration in individuals with cleft.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dens invaginatus such as radicular lingual groove always found in maxillary lateral incisor has higher prevalence in patients with CLP ( 37 ), it creates a pathological dental pocket. Such a pocket resulted from an infolding of the enamel into dentine destroys the connection between periodontal tissue and cementum and allows bacteria propagate within, which can't be easily removed ( 26 , 61 , 62 ).…”
Section: Mechanisms Linking Periodontitis and Clpmentioning
confidence: 99%
“…In favor of this connection are the epidemiological studies that show a higher frequency of dental anomalies in NSOC patients and unaffected relatives, and the genetic studies that show similarly altered genes and pathways in NSOC and dental anomalies. The connection between dental anomalies and NSOC is reviewed by das Neves et al, 2022. Initially, the authors report the frequencies of the most common dental anomalies in patients with NSOC and describe the candidate genes shared by these conditions.…”
Section: Figurementioning
confidence: 99%